The functional post-op rehabilitation results in the trimalleolar ankle fracture: A one-year follow-up of the case - Nazım Tolgahan Yildiz; Hikmet Kocaman; Gürsoy Coşkun; Nilgün Bek (National Scientific Medical Center, 2021)
The aim of this study was to evaluate the one-year results of the effects of an eight-week functional rehabilitation program on pain, swelling, range of motion, balance, fear of movement, functional status of the ankle, and quality of life in a patient with a surgically treated trimalleolar ankle fracture. In the study, pain (Visual Analogue Scale), ankle joint swelling (Figure of eight methods), range of motion (Universal goniometer), static balance performance (Flamingo Balance Test), fear of movement (Tampa Kinesophobia Scale), functional status of the ankle (Foot Function Index) and quality of life (SF-36 Health Survey) were assessed. An eight-week functional rehabilitation program was applied to the patient after 8th week from surgery. Assessments were repeated before and after functional rehabilitation program, and at the one-year follow-up. At the end of the functional rehabilitation program and in one-year follow-up, it was found that pain, swelling, and fear of movement decreased, range of motion, balance, functional status of the ankle, and quality of life increased. In trimalleolar ankle fractures, a well-planned functional physiotherapy and rehabilitation program after surgery can support surgical treatment by reducing the patient's symptoms and fear of movement, increasing functional capacity and quality of life.